Toxoplasmosis outbreak in sheep in northern-central Paraná, Brazil - Juliana Correa Bernardes; Fernanda Pinto-Ferreira; Luiz Daniel de Barros; Winni Alves Ladeia; Marcelle Mareze; João Pedro Sasse; Ana Flávia Minutti; Felippe Danyel Cardoso Martins; João Luis Garcia; Italmar Teodorico Navarro (Semina: Ciências Agrárias, 2021)
In this study, we aimed to investigate an outbreak of abortion in a herd of beef sheep on a property in Ivaiporã, north central Paraná, Brazil. A total of 64 blood samples were collected from the sheep, 33 of which were mothers with reports of abortion or stillbirth, and 7 with weak lamb birth. For epidemiological investigation of the parasite, fourteen samples were collected from different sources on the property, six from water, three from soil, one from trough, and four from feed. Indirect immunofluorescence (IFI) analysis and polymerase chain reaction were performed for detecting anti-Toxoplasma gondii antibodies in the sheep and molecular identification of the protozoan in the environment, respectively. The IFI results showed that 95.3% of the sheep were seropositive for anti-T. gondii antibodies; however, the environmental samples tested negative. During the visit to the property and interview with the owner, free-roaming cats were observed on the property for biological control of rodents that had access to the food deposits. This type of management may have triggered the outbreak, which reinforces the importance of preventive management and veterinary medical monitoring on sheep farms.